Stressful life events and alcohol consumption in elderly - Salazar Moreno, Carlos Alberto; Alonso-Castillo, María Magdalena; Armendáriz-García, Nora Angélica; Rodríguez-Puente, Linda Azucena (Horizonte Sanitario, 2022)
Objective: Determine the relationship between stressful life events and alcohol consumption in elders.Materials and methods: Correlational descriptive study, in 39 participants from Santa Catarina, Nuevo León, Mexico. A personal data record, the Stress Inventory in the Life of Older Adults and the Michigan Alcoholism Screening Test-Geriatric Version were applied.Results: 82.1% of participants were females, there were differences in the means of the alcohol consumption score according to sex (U = 70.00, p < 0.05). The events that were related to alcohol consumption were the death of a son (rs = .393, p = .013), the deterioration of the financial state (rs = .342, p = .033), the change to a less comfortable house (rs = .560, p = .000) and the loss of a friend rs = .409, p = .010).Conclusions: Stressful events can negatively impact AM and influence alcohol consumption as a coping strategy.Key words: Aged; Alcohol drinking; Stress psychological.